Unbending cane Pablo Manlapit, a Filipino labor leader in Hawaii - Kerkvliet, Melinda Tria (University of Hawai'i Press, 2018)
Unbending Cane not only provides a well-researched and accurate historical account of one of the most controversial labor leaders to come out of Hawaii before World War II, but also explores the complex layers of the man who took on the powerful sugar barons to seek justice for those working in Hawaii's cane fields.